Permeation properties of HDPE geomembranes - Pereira, D. S.D.; Lodi, P. C. [UNESP] (My University, 2010)
This paper evaluates the permeation properties of HDPE geomembranes intacts and after exposure to UV rays (weathering) after 12 years. Water vapor transmission tests (WVT) were performed in HDPE geomembranes (1.00 mm). Fresh and exposed samples were evaluated without imperfections and with holes of 1.6 and 3.0 mm. The goal of the imperfections and the UV degradation is the evaluation of the increase in the flux of the geomembrane. Results show, for instance, that the hole of 3.0 mm presented an increase about 650% in the values (fresh samples).
Keywords: Geomembranes; Permeation; UV degradation